Female top management in family firms and non-family firms: evidence from total population data. (2018) - Andersson, Fredrik W.; Johansson, Dan; Karlsson, Johan; Lodefalk, Magnus; Poldahl, Andreas
We exploit information on ownership, management and kinship to study the representation of women in top management teams in Swedish family and non-family firms among domiciled limited liability firms over the years 2004 to 2010. The share of female top managers is analysed across listed and non-listed firms as well as across industries. We then estimate the likelihood that a woman is elected into the top management team in family and non-family firms using a probit regression model where we control for firm- and individual-level characteristics, including the gender distribution of the firm and kinship relations to existing board members and firm owners. We find that non-listed family firms are more likely to appoint female top managers, whereas we find no differences among listed firms. Moreover, we find that the gender composition and kinship structures of firms influence the appointment of female top managers.